Boganmeldelser - Hans Kristian Bjerke; Peter Garde; Henrik Stevnsborg; Flemming Balvig; Margaretha Järvinen; Britta Kyvsgaard; Unni Bille-Brahe; Michael Boolsen; Hans Henrik Brydensholt; Henrik Garlik Jensen; Elmo Due; Vagn Greve (Nordisk Tidsskrift for Kriminalvidenskab)
Book reviews